Evaluation of PMA‐qPCR methodology to detect and quantify viable Shiga toxin‐producing Escherichia coli in beef burgers - Rey, Maria De Los Angeles (2021)
Propidium monoazide (PMA) is a selective nucleic acid intercalating dye that can be combined with real‐time PCR (qPCR) in order to evaluate cell viability in food samples. The aim of the present work was to evaluate PMA‐qPCR to detect and quantify viable STEC cells in beef burgers using stx2 as target gene. First, it was determined that 100 µM of PMA could inhibit qPCR signal from non‐viable cells and had no influence on the amplification of different concentrations of viable cells. Then, it was shown that PMA efficiently distinguished between different log cfu of viable cells in presence of a high concentration of non‐viable cells, both in culture and in beef burger homogenates. Finally, it was determined that PMA could distinguish between viable and non‐viable cells within the same log cfu in beef burger homogenates. PMA‐qPCR effectively detected and quantified viable STEC cells in culture and in beef burger homogenates.